Effects of geolocators on hatching success, return rates, breeding movements, and change in body mass in 16 species of Arctic-breeding shorebirds - Weiser, Emily L.; Lanctot, Richard B.; Brown, Stephen C.; Alves, José A.; Battley, Phil F.; Bentzen, Rebecca; Bêty, Joël; Bishop, Mary Anne; Boldenow, Megan; Bollache, Loïc; Kwon, Eunbi; Sandercock, Brett K. (My University, 2016)
Background: Geolocators are useful for tracking movements of long-distance migrants, but potential negative effects on birds have not been well studied. We tested for effects of geolocators (0.8–2.0 g total, representing 0.1–3.9 % of mean body mass) on 16 species of migratory shorebirds, including five species with 2–4 subspecies each for a total of 23 study taxa. Study species spanned a range of body sizes (26–1091 g) and eight genera, and were tagged at 23 breeding and eight nonbreeding sites. We compared breeding performance and return rates of birds with geolocators to control groups while controlling for potential confounding variables. Result: We detected negative effects of tags for three small-bodied species. Geolocators reduced annual return rates for two of 23 taxa: by 63 % for semipalmated sandpipers and by 43 % for the arcticola subspecies of dunlin. High resighting effort for geolocator birds could have masked additional negative effects. Geolocators were more likely to negatively affect return rates if the total mass of geolocators and color markers was 2.5–5.8 % of body mass than if tags were 0.3–2.3 % of body mass. Carrying a geolocator reduced nest success by 42 % for semipalmated sandpipers and tripled the probability of partial clutch failure in semipalmated and western sandpipers. Geolocators mounted perpendicular to the leg on a flag had stronger negative effects on nest success than geolocators mounted parallel to the leg on a band. However, parallel-band geolocators were more likely to reduce return rates and cause injuries to the leg. No effects of geolocators were found on breeding movements or changes in body mass. Among-site variation in geolocator effect size was high, suggesting that local factors were important. Conclusions: Negative effects of geolocators occurred only for three of the smallest species in our dataset, but were substantial when present. Future studies could mitigate impacts of tags by reducing protruding parts and minimizing use of additional markers. Investigators could maximize recovery of tags by strategically deploying geolocators on males, previously marked individuals, and successful breeders, though targeting subsets of a population could bias the resulting migratory movement data in some species.
Additional Authors: Bruce Casler; Maureen Christie; Jonathan T. Coleman; Jesse R. Conklin; Willow B. English; H. River Gates; Olivier Gilg; Marie-Andrée Giroux; Ken Gosbell; Chris Hassell; Jim Helmericks; Andrew Johnson; Borgný Katrínardóttir; Kari Koivula; Jean-Francois Lamarre; Johannes Lang; David B. Lank; Nicolas Lecomte; Joe Liebezeit; Vanessa Loverti; Laura McKinnon; Clive Minton; David Mizrahi; Erica Nol; Veli-Matti Pakanen; Johanna Perz; Ron Porter; Jennie Rausch; Jeroen Reneerkens; Nelli Rönkä; Sarah Saalfeld; Nathan Senner; Benoît Sittler; Paul A. Smith; Kristine Sowl; Audrey Taylor; David H. Ward; Stephen Yezerinac
Citation: Weiser, E.L., R.B. Lanctot, S.C. Brown, J.A. Alves, P.F. Battley, R. Bentzen, J. Bêty, M.A. Bishop, M. Boldenow, L. Bollache, B. Casler, M. Christie, J.T. Coleman, J.R. Conklin, W.B. English, H.R. Gates, O. Gilg, M.-A. Giroux, K. Gosbell, C. Hassell, J. Helmericks, A. Johnson, B. Katrínardóttir, K. Koivula, E. Kwon, J.-F. Lamarre, J. Lang, D.B. Lank, N. Lecomte, J. Liebezeit, V. Loverti, L. McKinnon, C. Minton, D. Mizrahi, E. Nol, V.-M. Pakanen, J. Perz, R. Porter, J. Rausch, J. Reneerkens, N. Rönkä, S. Saalfeld, N. Senner, B. Sittler, P.A. Smith, K. Sowl, A. Taylor, D.H. Ward, S. Yezerinac, and B.K. Sandercock. 2016. Effects of geolocators on hatching success, return rates, breeding movements and change in body mass in 16 species of Arctic-breeding shorebirds. Movement Ecology 4: art12. URL: http://movementecologyjournal.biomedcentral.com/articles/10.1186/s40462-016-0077-6
Keywords: Breeding success; Geologger; Global location sensor (GLS); Research impacts; Return rates; Tracking methods